Tinjauan Kelancaran Arus Lalu Lintas pada Area Bundaran Simpang Barelang di Wilayah Batu Aji Batam dengan Menggunakan Metode Manual Kapasitas Jalan Indonesia 1997 - Mada Surya Darmawan; Jody Martin Ginting; Usmanul Hayadi Umar (Kadiri University, 2022)
Smooth transportation conditions can improve population mobility services and other resources that can support economic growth. However, in densely populated cities like Batam, congestion often occurs and causes road users to feel stressed, the pace of the economy is hampered, and a lot of time is wasted. Therefore, it is necessary to review the performance of transportation. The purpose of this study was to determine whether the traffic performance at the Barelang intersection roundabout has been effective against the existing traffic situation in the area. The research was conducted by conducting a traffic survey on the road at the Barelang intersection, Batam to obtain the number of vehicles passing through the Barelang intersection. The reference used in this study is MKJI 1997 with the analysis carried out on road capacity, traffic volume, and degree of saturation. The results obtained at the Barrelang intersection for the road segment from SP Plaza to Muka Kuning has a degree of saturation value of 0.72. As for the road from Muka Kuning to SP Plaza, the degree of saturation is 1.08. Based on MKJI it is determined that the value of the degree of saturation of a road segment should not be more than 0.75, it can be concluded that the road from SP Plaza to Muka Kuning is considered effective and for the road segment from Muka Kuning to SP Plaza it is not effective. The results of this study can be used as a reference in an effort to improve transportation performance.